Regenerative tourism: transforming mindsets, systems and practices - Dianne Dredge (Journal of Tourism Futures, 2022)
Purpose – The purpose of this paper is to examine the mindset shift, systems change and boundary spanning practices needed to transition to a regenerative approach in tourism. The paper seeks to deliver concrete ways to shift thinking and transition to a regenerative paradigm. Design/methodology/approach – This viewpoint paper defines regenerative tourism, explores its principles and the levers for driving transformational change in tourism. It outlines what a conscious approach to regenerative tourism entails and outlines working principles for regenerative tourism. The paper concludes by identifying five key areas for reflection that seek to challenge established thinking and practice. Findings – The reinvention of tourism requires work in three key areas: systems change, mindset shift and practice. Three findings are summarised as: (1) Regenerative tourism requires a shift in social-ecological consciousness and depends on our capacity to evolve our thinking from “me” to “we” and to develop compassion, empathy and collaborative action. (2) Scientific management is inconsistent with the transition to regeneration. Tourism must be managed as a complex adaptive system and overcome the challenges of individualism, reductionism, separation and marketisation associated with scientific thinking. (3) Regenerative tourism requires a deeply engaged bottom-up approach that is place-based, community-centred and environment-focused. Originality/value – This paper shares the reflections, working principles and recommendations of The Tourism CoLab and is based on 30 years of experience as a consultant, policy analyst, educator, researcher, professor and now as founder of two tourism social enterprises. With the luxury of reflection and the distance from higher education that many do not have, the author shares her approach to shifting mindsets and driving transformative change.